Safety and efficacy of mini-percutaneous nephrolithotomy(PCNL) in renal or upper ureteric stone >1cm - Khwaunju, Pragyan; Tamrakar, Kishor Kumar; Sah, Keshar Bahadur; Bhattarai, Abhishek; Piya, Bimochan; Regmi, Bharati (Journal of Chitwan Medical College, 2017)
Abstract available on the PDF.